(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The petrochemical industries have recently given refractory castable improved with nano bonding a lot of attention. The properties of the castable material have been improved by the use of different binders and sintering additives. Numerous research projects are now looking at use of different nano binders, such colloidal alumina and silica in conjunction with sintering additives like those based on aluminium or boron. The objective is to reduce energy use and enhance densification. In order to improve both thermal and mechanical characteristics, nano-structured binders in particular colloidal silicaare also being investigated with a variety of raw materials, including fused silica, tabular alumina and mullite.The green strength of these nano-bonded castables is further increased by the use of setting or gelling chemicals. This review focuses on the potential of setting agents like HA and CAC, sintering additives (primarily boron-based), and nanostructured binders like colloidal silica and colloidal alumina in high alumina refractory castables intended for use in petrochemical industries, particularly FCC units.